A STUDY ON THE ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF RIAU UNIVERSITY IN UNDERSTANDING THE MEANING OF PHRASAL VERBS - Army, Fauziah Army Fauziah; Delfi, Syofia Delfi Syofia; ', Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objective of this descriptive research was to find out about students’ ability in understanding meaning of phrasal verbs. The sample of this research was the fourth semester students of English Department of Riau University. There were 38 students participate as the sample of this research. The data were quantitative and the instrument of the research was a set of multiple choice test which consist of 50 questions regarding the meaning of phrasal verbs. The data were analyzed by calculating the score of the students in answering the test and classifying them to a certain level of ability using Harris formula. The results were that out of 38 students, 2 students (5.26%) were in excellent level of ability, 11 students (28.95%) were in good level of ability, 7students (18.42%) were in average level of ability, and for the most part, 18 students(47.36%) were in poor level of ability. In addition, the average score of the students in understanding meaning of phrasal verbs was 51.37. It meant that the students’ ability in understanding meaning of English phrasal verbs was in the average level of ability. This research recommended the students to make themselves familiar with more elaborated use of phrasal verb. Students can also comprehend more about the conceptualization of phrasal verbs in many contexts by practicing writing and speaking that would require them to use phrasal verbs. Further research can focus on studying each subtopic in detais. Other researchers can also focus on how to overcome the high level of difficulties of English phrasal verbs materials.Keywords: ability, understanding, phrasal verbs